The Role of Urban Trees in Reducing Land Surface Temperature - Yaşlı, Ruken; Yücedağ, Cengiz; Ayan, Sezgin; Simovski, Bojan (Prensip Publishing, 2023)
Increasing urbanization in the world in recent years has resulted in the replacement of areas covered with plants by buildings. Because of this change, urban areas are warmer than rural areas (urban heat island). In this investigation, the urban heat island (UHI) effect, the methods of combating this effect and notably the role of urban trees are exhaustively elaborated by considering the relevant literature. In addition, suggestions were made on which species should be selected and how tree species should be positioned to reduce UHI effect. There are solid evidences that trees, urban green spaces and wider green infrastructure can bring significant reductions in urban temperatures. Urban planners and decision makers can help combat UHI and increase urban resilience to the effects of climate change, primarily by planting the urban environment with extensive shade-providing species and harnessing the most of the opportunities afforded by restoration activities. Trees and other vegetation can cool the surrounding air by evapotranspiration thanks to both transpiration from plant leaves and evaporation of water from irrigated soil. The tree canopy can considerably improve outdoor thermal comfort by preventing a pedestrian from being exposed to solar radiation, and also by protecting floors and building coverings from UHI effect. Furthermore, if a roadside afforestation is to be established to combat UHI effect, a proper plan based on the character of the road will be beneficial in terms of achieving the determined goals. Eventually, the adaptation to UHI should be achieved to plan short-, medium- and long-term changes.
Review article
Keywords: Cooling; Urban heat island; Urban trees; Woody species selection